Pengaruh Pertumbuhan Ekonomi dan Pengeluaran Pemerintah Terhadap Pendapatan Asli Daerah pada Pemerintah Daerah Kabupaten Aceh Tenggara Tahun 2017-2021 - Rina Malahayati; Deni Trianda Pitri; Julianti Julianti (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to find out how big the influence of economic growth and government expenditure is on regional own-source income in the Regional Government of Southeast Aceh District from 2017-2021. This research includes associative research. The population of this study is the Regional Government of Southeast Aceh Regency from 2017 to 2021. This research uses the census method. Data analysis techniques using path analysis. The results of the study show that economic growth has a positive effect on regional original income and government spending has a negative effect on regional original income